1983
DOI: 10.1111/j.1365-2141.1983.tb02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of bone marrow fibroblastoid stromal cells in mice via the intravenous route

Abstract: Kinetics of fibroblastic colony-forming cells (CFU-F) were studied in mouse bone marrow after lethal total body irradiation and intravenous bone marrow transplantation. After an initial decrease, CFU-F numbers recovered, and plateaued 5 weeks post-treatment at 10% of normal values. Using chromosome-marked donor bone marrow cells we found that 1 day after transplantation 72% of donor CFU-F had reached the recipient's bone marrow, indicating a highly specific lodgment of CFU-F. Three months after transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 9 publications
3
43
0
Order By: Relevance
“…Evidence for this has come largely from analysis of adherent 'stromal' cells in long-term cultures of bone marrow derived from allogeneic marrow transplant recipients in both animals (Friedenstein et al, 1978;Bentley et al, 1982;Chertkov et al, 1985;Perkins & Fleischman, 1988) and humans (Golde et al, 1980;Laver et al, 1987;Simmons et al, 1987). However, similar studies in both humans (Keating et al, 1982;Piersma et al, 1983) and mice (Marshall et al, 1984) (Fialkow et al, 1980;Fialkow, 1983;Singer et al, 1984). These results suggested that a common stem cell may exist for both haemopoietic and stromal cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for this has come largely from analysis of adherent 'stromal' cells in long-term cultures of bone marrow derived from allogeneic marrow transplant recipients in both animals (Friedenstein et al, 1978;Bentley et al, 1982;Chertkov et al, 1985;Perkins & Fleischman, 1988) and humans (Golde et al, 1980;Laver et al, 1987;Simmons et al, 1987). However, similar studies in both humans (Keating et al, 1982;Piersma et al, 1983) and mice (Marshall et al, 1984) (Fialkow et al, 1980;Fialkow, 1983;Singer et al, 1984). These results suggested that a common stem cell may exist for both haemopoietic and stromal cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…A donor origin for these cells suggests that there is a common stem cell for both haemopoietic and stromal cell systems in the marrow. Support for this concept has come from both cytogenetic and enzyme marker studies of adherent stromal cells in long-term marrow cultures derived from allogeneic transplant recipients (Keating et al, 1982;Piersma et al, 1983;Marshall et al, 1984). However, results of similar in vitro experiments in both animals (Friedenstein et al, 1978;Bentley et al, 1982;Chertkov et al, 1985;Perkins & Fleischman, 1988) and humans (Golde et al, 1980;Laver et al, 1987;Simmons et al, 1987) have shown a host origin for stromal cells, suggesting that a common precursor cell does not exist for both systems.…”
mentioning
confidence: 99%
“…CFU-F of donor origin were detected in the bone marrow of irradiated mice after bone marrow transplantation. 28 Engraftment of a clonal murine bone marrow stromal cell line in irradiated mice has been described, which stimulated hematopoietic recovery after total body irradiation. 29 Donor stromal cells were detected only in the bone marrow of recipients but other studies indicate an ability for bone marrow stromal cells to engraft other tissues as well.…”
Section: Figurementioning
confidence: 99%
“…Our data are in good agreement with previously published reports demonstrating that after syngeneic or xenogeneic transplantation of MSCs derived from the bone morrow of mouse, rat or nonhuman primates, donor cells engraft into many tissues of conditioned recipients. [53][54][55][56][57] It is still unclear whether transplanted cells continue to retain their multilineage potentials and clonogenic ability or if they were able to commit into residing tissue. At present, Overall, our results provide evidence supporting the suitability of genetically corrected MSCs by ODN in cellbased therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%